The Profile of Pedagogical Competence of English Teachers at SMPN 1 Liukang Kalmas - Auliyaputri, Nurul; Talib, Ahmad; Muhayyang, Maemuna (Journal of Excellence in English Language Education, 2025)
This research aims to find out the profile of pedagogical competence of English. The subject of the research was two English teachers at SMPN 1 Liukang Kalmas. This research used a descriptive qualitative method. The interview and documentation were used as the main tools to collect data. The results of this research showed that the two English teachers demonstrated good in organizing educational development activities due to: (1) In implementing learning activities English teachers’ lessons begin with prayer, apperception, motivation, and clear objectives, setting a positive tone. (2) In responding to learners’ mistakes as stages of the learning process teachers constructively respond to students' mistakes, offering support and rewards that enhance motivation and confidence. (3) In classroom management English teachers’ cooperative classroom atmosphere is fostered through rotating group activities, keeping students engaged. (4) In providing opportunities for learners to express opinions in discussion. The teachers also facilitate interactive discussions, and group problem-solving, and address challenges like limited internet access, ensuring sustained student enthusiasm and optimal learning outcomes.